Answer: (-4, -1)
This means x = -4 and y = -1 pair up together.
======================================================
You're on the right track. You'll replace the 'x' with 3y-1, but you made a typo. I think you meant to write the subtraction symbol instead of the equal sign.
Here's what your steps could look like
-2x + 5y = 3
-2(3y-1) + 5y = 3
-6y + 2 + 5y = 3
-y + 2 = 3
-y = 3-2
-y = 1
y = -1
x = 3y-1
x = 3(-1) - 1
x = -3-1
x = -4
Therefore, (x, y) = (-4, -1) is the solution
-------------------
As the steps above show, I replaced each copy of x in the second equation with (3y-1). This is due to x = 3y-1. From there, we isolate y. Once you determine that y = -1, it's plugged into the first equation to find x.
If you were to graph x = 3y-1 and -2x+5y = 3 on the same xy coordinate grid, then the two lines would intersect at (-4, -1)
Also, note how plugging x = -4 and y = -1 into the second equation leads to...
-2x+5y = 3
-2(-4)+5(-1) = 3
8 - 5 = 3
3 = 3
We get the same value on both sides, so that verifies the second equation. I'll let you verify the first equation.